COMMUNITY PERCEPTIONS OF THE NATIONAL AGRARIAN OPERATION PROGRAM (PRONA) BY FULL SYSTEMIC LAND REGISTRATION (PTSL) ALESIPITTO VILLAGE, MA'RANG DISTRICT, PANKEP REGENCY - Marsuki Marsuki (Sean Institute, 2022)
This study was to determine the community's perception of the National Agrarian Project Program (PRONA) by the complete systematic land registration (PTSL) in Alesipitto Village and the factors that influence it. The purpose of the study was to determine the public's perception of the national agrarian program by complete systematic land registration in Alesipitto Village, Ma'rang District, Pangkep Regency. The research method used is a quantitative method. The sampling technique used accidental sampling with a total of 50 samples of respondents. Data processing carried out by researchers using the SPSS Version 20 program. The results of measuring public perceptions of PRONA by PTSL registration in Alesipitto Village according to respondents' responses have gone well with the percentage value of community perceptions about the program Prona by 72%.